2005
DOI: 10.1039/b416478d
|View full text |Cite
|
Sign up to set email alerts
|

Following FRET through five energy transfer steps: spectroscopic photobleaching, recovery of spectra, and a sequential mechanism of FRET

Abstract: Abstract:We report the acquisition and analysis of spectrally resolved photobleaching data from a model system designed to exhibit FRET. Spectrally resolved photobleaching can be used to determine the presence of FRET in these systems and to investigate multi-step mechanisms of energy transfer. The model system was a previously described set of fluorescent beads consisting of a system of 6 fluorophores. In standard photobleaching experiments to determine FRET, bleaching of an acceptor molecule resulting in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The T-8869 beads consist of a system of six BODIPY dyes emitting at 720, 678, 635, 592, 560 and 515 nm. Under normal conditions, these microspheres exhibit highly efficient energy transfer along a series beginning with the first donor (515 nm) to the terminal acceptor (720 nm) (Roberts et al 1998;Forde & Hanley 2005) The assumption of no competing dark processes is equivalent to assuming that the quantum yields of both the donor and acceptor are 1. If the acceptor transfers 50 per cent of its energy via FRET to a subsequent acceptor then the amount of light observed from the first acceptor will be one-half of that from the principal donor.…”
Section: Energy Transfer and Allowed Regions In Ab-spacementioning
confidence: 99%
“…The T-8869 beads consist of a system of six BODIPY dyes emitting at 720, 678, 635, 592, 560 and 515 nm. Under normal conditions, these microspheres exhibit highly efficient energy transfer along a series beginning with the first donor (515 nm) to the terminal acceptor (720 nm) (Roberts et al 1998;Forde & Hanley 2005) The assumption of no competing dark processes is equivalent to assuming that the quantum yields of both the donor and acceptor are 1. If the acceptor transfers 50 per cent of its energy via FRET to a subsequent acceptor then the amount of light observed from the first acceptor will be one-half of that from the principal donor.…”
Section: Energy Transfer and Allowed Regions In Ab-spacementioning
confidence: 99%
“…5a). In contrast to the extensively characterized T-8869 beads (17,27), the T-8883 beads do not transfer energy primarily to a single terminal acceptor. At the beginning of the experiment, evidence of three dyes was readily observed.…”
Section: Spectroscopic Lifetime Analysis Of Beads Exhibiting Energy Tmentioning
confidence: 99%
“…Spectral imaging with a prism-based spectrograph during photobleaching allows simultaneous observation of multiple fluorescent dyes (17). The advantage is that FRET relationships between the dyes can be determined, and parallel processes can be looked at in isolation.…”
Section: Imaging Spectroscopic Photobleachingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with suitable chromophore differentiation, functionally unidirectional transfer is exhibited in multichromophore systems, assisted by suitable chromophore disposition, and often the operation of a spectroscopic gradient. Through experimental studies involving photobleaching spectroscopy, it has recently been shown possible to trace the intricate form of such multi-step resonance energy transfer [13], allowing sequential mechanisms to be established in kinetically and spectroscopically complex systems. Whilst the principles that govern the directionality of energy flow in multichromophore systems is largely understood, other recent developments have identified new possibilities for effecting externally determined directional control.…”
Section: Introductionmentioning
confidence: 99%